THE ROLE OF OCB GREEN EMPLOYEES IN SUPPORTING THE IMPLEMENTATION OF THE SIGI GREEN REGIONAL REGULATION IN THE ENVIRONMENTAL SERVICE OF SIGI REGENCY - Risnawati; Lina Mahardiana; Faruq Lamusa; Octhavianny Mercynta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The implementation of local environmental policies is not solely determined by formal regulations , but also by the discretionary behavior of public employees as policy implementers . This study aims to analyze the role of Organizational Citizenship Behavior for the Environment (OCB Green) in supporting the implementation of Sigi Regency Regulation No. 4 of 2019 on Sigi Hijau at the Environmental Agency of Sigi Regency. A qualitative descriptive approach with a constructivist paradigm was employed . Data were collected through in- depth interviews , field observations , and document analysis involving eight informants selected using snowball sampling. Thematic analysis was conducted based on three OCB Green dimensions : eco- initiatives , eco- helping , and eco- civic engagement . The findings reveal that policy implementation is significantly strengthened by employees ' extra-role behaviors . Eco- initiatives enhance internalization of environmental values , eco- helping reinforces a green organizational culture , and eco- civic engagement extends policy impacts to the community . These results indicate that OCB Green functions as an informal mechanism bridging formal policy and practical implementation , thereby improving the effectiveness of local environmental governance